Electronic Money Card Service User Loyalty in Payment Transactions: A Study on Generation Z Students - Olfebri, Olfebri; Yuliantini; Ika Utami Yulihapsari; Primadi Candra Susanto (Dinasti Publisher, 2025)
This study aims to determine factors that influence the quality of service and the loyalty of electronic card service users, particularly in making payment transactions.The study used a quantitative-descriptive research method, collecting primary data from 560 electronic money card users at XYZ University. The sample included 131 users, and the data was analyzed using SmartPLS 3.0. The data was presented as numbers and interpreted into descriptions.This study indicates that: 1) ease of transaction has a positive and significant effect on service quality; 2) ease of transaction has a positive and significant effect on customer loyalty; 3) perceived Security has a positive and significant effect on service quality; 4) perceived security has a positive and significant effect on customer loyalty; 5) service quality has a positive and significant effect on customer loyalty; 6) ease of transaction has a positive and significant effect on customer loyalty through service quality; and 7) perceived security has a positive and significant effect on customer loyalty through service quality.This investigation has the potential to offer novel perspectives on the quality of service and customer loyalty among electronic money card users.